2013
DOI: 10.1080/14786451.2013.826223
|View full text |Cite
|
Sign up to set email alerts
|

Fault diagnosis of photovoltaic modules through image processing and Canny edge detection on field thermographic measurements

Abstract: Today, conventional condition monitoring of installed, operating photovoltaic (PV) modules is mainly based on electrical measurements and performance evaluation. However, such practices exhibit restricted fault-detection ability. This study proposes the use of standard thermal image processing and the Canny edge detection operator as diagnostic tools for module-related faults that lead to hot-spot heating effects. The intended techniques were applied on thermal images of defective PV modules, from several fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(81 citation statements)
references
References 31 publications
0
80
0
1
Order By: Relevance
“…They are hard to avoid and it is impossible to quantify their impact on module's performance during their lifetime. In the literature [5], it is reported that as a field module ages and is subjected to thermal and mechanical stresses, repeated relative movement of the crack results in electrical separation and an inactive cell with significant hot spot heating effect.…”
Section: Infrared Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…They are hard to avoid and it is impossible to quantify their impact on module's performance during their lifetime. In the literature [5], it is reported that as a field module ages and is subjected to thermal and mechanical stresses, repeated relative movement of the crack results in electrical separation and an inactive cell with significant hot spot heating effect.…”
Section: Infrared Imagingmentioning
confidence: 99%
“…A number of studies in the literature [5,12] have reported the defects associated with fielded PV modules as well as in recently installed modules [16,17] using optical and thermal observations. According to IEC 61215 and as reported in the literature [18], the parameters for detecting degradation include defects in insulation and leak currents and visual detection.…”
Section: Low and High Short Circuit Current And Open Circuit Voltagementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the least square method is used to fit the gray level histogram. The gray level histogram provides us with 256 sample points whose coordinates are seen as formula (2) : Based on the characteristics of infrared thermal image of PV module , we can select gray value corresponding to the first 'valley' on the right hand side of the highest peak as the segmentation threshold, so that the hot spots can extracted .The threshold T is set according to formula (4).…”
Section: Introductionmentioning
confidence: 99%
“…Tsanakas, etc. proposes the use of standard thermal image processing and the Canny edge detection operator as diagnostic tools for module-related faults that lead to hot-spot heating effect [4] . Wang Pei-zhen presents a new method of target feature extracting in view of low contrast of target and background, strong noise and non uniformity in the infrared image and peculiarity of the photovoltaic array.…”
Section: Introductionmentioning
confidence: 99%